Strategic outsourcing's role in driving economic value by examining mediating role of organizational capabilities and sustainable innovation - Shi, Lei (Frontiers in Psychology, 2022)
The study's overarching purpose was to investigate the impact of Strategic HR outsourcing on organizational sustainability. This study also attempted to evaluate the function of organizational capabilities and HR proficiency as a mediator in the relationship between Strategic HR outsourcing and organizational sustainability. Data was collected from 400 HR professionals in China using a questionnaire technique. The Smart PLS software and a structural equation modelling (SEM) technique were used to evaluate the data. Organizational sustainability was found to be insignificantly related tostrategic HR outsourcing. Furthermore, organizational capabilities and HR proficiency were discovered to mediate the association between strategic HR outsourcing and organizational sustainability. By analyzing the impact of strategic HR outsourcing on organizational sustainability, this paper provided an important theoretical contribution. In terms of practical applications, this article would surely help the HR professionals to maintain and develop policies to encourage employees to be engaged and perform well. Furthermore, this study might be effective in resolving difficulties linked to organizational sustainability. The small sample size of this study, which included solely HR professionals working in the Chinese firms, was one of its limitations.In addition, future study can incorporate other constructs to acquire a deeper knowledge of the factors that influence employee health.